THE DEVELOPMENT OF AN ALTERNATIVE GROWTH CHART FOR ESTIMATED FETAL WEIGHT IN THE ABSENCE OF ULTRASOUND: APPLICATION IN INDONESIA - Felicia Beta Papilaya (Faculty of Medicine Universitas Kristen Duta Wacana, 2021)
Various development of fetus can be monitored by ultrasound, including estimated fetal weight. Estimated fetal weight is used to estimate the expected (normal) birth weight and it is also one of the critical indicators for assessing fetal risk during pregnancy. Meanwhile, ultrasound is not always available in health care centers in Indonesia. In this journal, Anggraini et al conducted a study to develop growth chart used to predict fetal weight in the absence of ultrasound. The study consists of several steps. The first step is a comparison study that took place in South Kalimantan, Indonesia, involving 19 pregnant women. This was carried out between the existing and the proposed models. The existing models were developed based on data recorded within one week of delivery and within 14 days of the last ultrasound scan, while the proposed model: EFW (g) = 109.16FH -272 [Eq.1] was developed based on FH measurement recorded between 35 and 41 weeks (before delivery) and actual birth weight. The results show that the proposed model is significantly more capable (less error) than the existing models in predicting fetal weight during pregnancy, even at earlier GAs. It also can be seen that the prediction errors are less pronounced when the pregnancy reaches advanced GAs. The second step is a study that aims to develop an alternative fetal growth chart for EFW that does not use an ultrasound-based weight prediction model, the proposed clinical model, based only on FH measurement [Eq (1)], was used to estimate the fetal weight at a given GA. A total of 402 women are participating in this study. In this research, the proposed clinical quadratic EFW-GA model: EFW = 137.173GA - 1:035 GA2 - 675:199 [Eq.2] was used to develop the chart. This model was compared with the existing model through several analysis. Overall, this study shows that the proposed clinical model is more reliable than the existing model in predicting fetal weight. It is even more effective at earlier GAs than the existing models. Therefore, the proposed model could be an alternative model to estimate fetal weight and develop a suitable fetal growth chart. This alternative chart is going to be significantly useful for health care workers to do fetal risk assessment during pregnancy in rural areas with low resources, so that fetal growth abnormalities can be reduced. At this point, this study will also help the government to reduce neonatal mortality.